Fig. 4 in Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract ... - Mecca, Silvia; Casoli, Edoardo; Ardizzone, Giandomenico; Gambi, Maria Cristina (Zenodo, 2020)
Fig. 4: Percentage of different types of biological apex erosion (Sarpa salpa, sea urchins, and crustaceans) during time at the studied stations and considering only the leaves showing biological erosion. ... : Published as part of Mecca, Silvia, Casoli, Edoardo, Ardizzone, Giandomenico & Gambi, Maria Cristina, 2020, Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract, pp. 70-83 in Mediterranean Marine Science 21 (1) on page 76, DOI: 10.12681/mms.20795, http://zenodo.org/record/12551640 ...